Experiences of Korean Medicine treatment in patients with Bell’s palsy: A qualitative study protocol - Eunbyul Cho; Seung Eun Chung; Sungha Kim (PLoS ONE, 2025)
Background Bell’s palsy significantly impacts patients’ quality of life, with approximately 30% not fully recovering. In South Korea, Korean Medicine (KM) is widely used as a complementary approach for facial palsy, with 50.86% of patients utilizing KM in 2021. Although quantitative studies have shown KM’s effectiveness, there is a lack of research on lived experiences of the participants on KM treatment. We aim to identify the meaning of using KM among the patients with Bell’s palsy. Methods This study will be conducted in compliance with the consolidated criteria for reporting qualitative research. Patients with Bell’s palsy who had or have received KM treatment and whose onset was less than two years prior to the interview date will be recruited by purposive and snowball sampling. One-on-one interviews will be conducted in person using a semi-structured interview guide. Interviews and recruitment will continue until meaning saturation is reached. The interviews will be conducted in South Korea in a private area near the patient’s residence to make them feel comfortable. The data will be analyzed using Colaizzi’s seven-step method. Discussion This study will explore the lived experiences of patients using KM for Bell’s palsy and seek to understand the essence of their experiences. Utilizing Colaizzi’s phenomenological approach, common themes in patients’ experiences of receiving KM treatment will be uncovered. The findings are expected to provide valuable insights into healthcare professionals, potentially enhancing clinical practice and patient-centered care in the treatment of Bell’s palsy.